HOW IS THE PRACTICE OF HUMAN RESOURCES CONTRIBUTE TO CREATING CUSTOMER SATISFACTION? - Marwan, Jubery (Moestopo International Review on Social, Humanities, and Sciences, 2023)
This study aims to answer the practice of human resource contribution to creating customer satisfaction. Organizations need to develop and expand organizational structures that enable participatory decision-making. Interaction between members of the organization requires emotional intelligence to stimulate the emergence of new ideas in understanding the main tasks and functions of the organization. This study uses a Likert scale in a questionnaire to obtain primary data. Of the 180 lecturers and education staff surveyed, 168 respondents gave answers. The research results show that; 1) Individual ability, work professionalism, organizational commitment, and knowledge sharing do not contribute significantly to emotional intelligence directly. But work discipline contributes significantly to emotional intelligence directly; 2) Individual ability, work discipline, and organization commitment do not contribute significantly to consumer satisfaction directly. But work professionalism, and knowledge sharing contribute significantly to consumer satisfaction directly; 3) Emotional intelligence contributes significantly to customer satisfaction directly; and 4) Human resources (individual abilities, work professionalism, work discipline, organizational commitment, and knowledge sharing) indirectly contribute to creating consumer satisfaction.